Recent Progress in Interconnection Layer for Hybrid Photovoltaic Tandems. Issue 51 (13th October 2020) - Ko, Yohan; Park, HyunJung; Lee, Chanyong; Kang, Yoonmook; Jun, Yongseok
Abstract: Hybrid tandem solar cells offer the benefits of low cost and full solar spectrum utilization. Among the hybrid tandem structures explored to date, the most popular ones have four (simple stacking design) or two (terminal/tunneling layer addition design) terminal electrodes. Although the latter design is more cost‐effective than the former, its widespread application is hindered by the difficulty of preparing an interface between two solar cell materials. The oldest approach to the in‐series bonding of two or more bandgap solar cells relies on the introduction of a tunneling layer in multijunction III–V solar cells, but it has some limitations, e.g., the related materials/technologies are applicable only to III–V and certain other solar cells. Thus, alternative methods of realizing junction contacts based on the use of novel materials are highly sought after. Here, the strategies used to realize high‐performance tandem cells are described, focusing on interface control in terms of bonding two or more solar cells for tandem approaches. The presented information is expected to aid the establishment of ideal methods of connecting two or more solar cells to obtain the highest performance for different solar cell choices with minimized energy loss through the interface. Abstract : The introduction of an intermediate layer to bridge different solar cell technologies, which have become mature for the optimization of single‐junction cells, is a critical technology for fabricating efficient hybrid tandem solar cells. The design and classification of an efficient interconnection layer that leverages the full potential of the hybrid tandems are discussed.